2021
DOI: 10.1016/j.sjbs.2021.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bioactive compounds and chemical composition of Malaysian stingless bee propolis water extracts

Abstract: Propolis is a resinous substance collected by stingless bees containing bioactive compounds which exert various biological properties. The present study focused on the evaluation of chemical profiles produced by three Indo-Malayan stingless bee propolis extracted using water. Fresh propolis was collected from the same area and ecosystem conditions in Selangor, Malaysia, namely Tetrigona apicalis , Tetrigona binghami , and Heterotrigona fimbriata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
1
11
1
2
Order By: Relevance
“…They also play a major part in the biological activities of the propolis essential oil extract, such as antimicrobial and anti-inflammatory activities [33]. The TTC in Indian propolis has been reported to be 1.5 to 3.8 LE mg/100 g, which is lower compared to our results [37]. The difference with our results can be attributed to the variation in vegetation.…”
Section: Discussioncontrasting
confidence: 95%
“…They also play a major part in the biological activities of the propolis essential oil extract, such as antimicrobial and anti-inflammatory activities [33]. The TTC in Indian propolis has been reported to be 1.5 to 3.8 LE mg/100 g, which is lower compared to our results [37]. The difference with our results can be attributed to the variation in vegetation.…”
Section: Discussioncontrasting
confidence: 95%
“…In contrast, honey bees use wax to construct their combs. This corroborates the report on stingless bees producing large amounts of propolis compared to any other bee species 7,8 …”
Section: Introductionsupporting
confidence: 91%
“…This corroborates the report on stingless bees producing large amounts of propolis compared to any other bee species. 7,8 The chemical composition of propolis is dependent on several factors such as geographical location, species of bees, resin preference, plant species availability, and individual plant resin compositions. 9,10 It contains waxes, polyphenols such as phenolic acids and flavonoids, terpenoids, and alkaloids with these contents being influenced by the vegetation at the site of collection.…”
Section: Introductionmentioning
confidence: 99%
“…The GC flame ionization detector (FID) will provide a Total Respond Chromatogram (TRC) and the MS will provide specific analysis results at each TRC point or peak. Each peak point indicates the type of compound contained in the propolis extract which was then adjusted according to the Library NIST Mass Spectrometry Reference Database 14 (Pobiega et al 2019;Salleh et al 2021).…”
Section: Determination Of Antioxidant Activity Of Propolis Extractmentioning
confidence: 99%
“…Previous studies of GC-MS analysis of propolis extract also reported similar results which revealed compounds such as sugars, carboxylic acids, terpenoids, sugar alcohols, hydrocarbons, aldehydes and amino acids. The main compound found in the propolis extract was sugar which is around 31.4% (Salleh et al 2021). Some types of reducing sugars include ribose, fructose, glucose, and galactose.…”
Section: Bioactive Compounds Of Propolismentioning
confidence: 99%